Industrial symbiosis concept applied to green hydrogen production: a critical review based on bibliometric analysis - José Cláudio Trindade Simões; Silvio Vaz Júnior (Discover Sustainability)
Abstract The use of fossil fuels has generated large amounts of greenhouse gas (GHG) emissions into the atmosphere, resulting in harmful environmental impacts. Faced with this situation, it is necessary to search for new sources of energy and fuels to mitigate the adverse effects of this excessive use and create opportunities for a cleaner energy transition. In this context, the production of green hydrogen (GH) stands out as an effective and more sustainable alternative, although it still faces obstacles to its wider use. These challenges can be solved with the application of industrial symbiosis (IS). The objective of this review was to identify the scenario and understand the application of the IS concept in GH production. To achieve this purpose, a bibliometric review of publications indexed in Scopus was carried out, also seeking to identify global positions in relation to the use of this technological approach. The results indicate that the theme presents emerging characteristics, such as the low concentration of data in a single author or country, characterizing a developing study concept. Graphical Abstract